JOURNAL jurnal perbankan syariah - Eva Febryana (Jurnal Ekonomi Bisnis Syariah, 2020)
Sharia banks are banks that are based on the principles of partnership, justice, transparency and universality and carry out banking business activities based on sharia principles as well as an implementation of Islamic economic principles. One of the sharia banks in Indonesia is PT. Bank Muamalat, Kolaka Sub-Branch Office. PT. Bank Muamalat, Kolaka Sub-Branch Office, has murabahah financing. In DSN-MUI Fatwa No 84 / DSN-MUI / XII / 2012 There are 2 methods of recognizing murabahah financing margins. namely the proportional method and the annuity method. For Islamic banks that apply the proportional method and the annuity method is carried out in accordance with the Fatwa DSN-MUINo 84 / DSN-MUI / XII / 2012 and PSAK 50, 55, and 102 So that if the Fatwa and PSAK are applied it can reduce the occurrence of unwanted risks. The results of this study indicate that PT. Bank Muamalat's Kolaka Sub-Branch Office in its murabahah financing margin recognition method applies the annuity method and is in accordance with PSAK 50, 55, and 102, as well as Fatwa DSN-MUI No 84 / DSN-MUI / XII / 2012.